2016
DOI: 10.1371/journal.pone.0167498
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of Retinol-Binding Protein 4 Are Associated with Breast Cancer Risk: A Case-Control Study

Abstract: BackgroundRetinol binding protein 4 (RBP4) is a recently identified adipokine that is elevated in patients with obesity or type 2 diabetes. A growing body of research has shown that RBP4 is associated with several types of cancer. However, no studies have investigated the relationship between serum RBP4 levels and breast cancer risk. We performed a case-control study to evaluate the association between serum RBP4 levels and the risk of breast cancer.MethodsFrom August 2012 to December 2013, four-hundred subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 60 publications
2
25
1
1
Order By: Relevance
“…A similar tendency (in the case of ER) was observed in our studies ( Figure S3H). However, in contrast to the studies of Jiao et al, our results showed significant differences in the plasma levels of RBP4 between patients with metastatic and nonmetastatic tumors [25]. Moreover, our animal studies on two sister cell lines, nonmetastatic 67NR and metastatic 4T1, confirmed significantly higher RBP4 plasma levels in mice bearing metastatic tumors than in mice bearing nonmetastatic tumors.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A similar tendency (in the case of ER) was observed in our studies ( Figure S3H). However, in contrast to the studies of Jiao et al, our results showed significant differences in the plasma levels of RBP4 between patients with metastatic and nonmetastatic tumors [25]. Moreover, our animal studies on two sister cell lines, nonmetastatic 67NR and metastatic 4T1, confirmed significantly higher RBP4 plasma levels in mice bearing metastatic tumors than in mice bearing nonmetastatic tumors.…”
Section: Discussioncontrasting
confidence: 99%
“…Although several studies have presented the analysis of the effect of RBP4 on several types of cancers, only one study has shown such research on patients with breast cancer [25]. In their case-control study, Jiao et al showed that serum RBP4 levels were positively associated with breast cancer risk among patients with lower BMI (<25 kg/m 2 ) and that patients with ER-or PR-negative tumors possessed significantly higher serum levels of RBP4 [25]. A similar tendency (in the case of ER) was observed in our studies ( Figure S3H).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated level of RBP 4 is reported previously in breast cancer. 22 In our case, the RBP 4 is also upregulated in smoker, COPD, and lung cancer. We have also noted that there is sequential increase of two proteins including haptoglobulin and alpha-1-antitrypsin from healthy, smoker, COPD to lung cancer.…”
Section: Discussionsupporting
confidence: 48%
“…We selected 7 SNPs dealing with immune response, metabolic factors, extracellular matrix and inflammatory pathways that have been suggested to be related to tumor development. Secondarily, we evaluated serum retinol levels that have been related to tumor development of different kinds [22,23,[45][46][47] and with the PNPLA3 variant I148M [21,24]. Surprisingly, we did not find any significant association between the majority of the selected SNPs and HCC development, nor between serum retinol levels and PNPLA3 variant I148M.…”
Section: Discussionmentioning
confidence: 79%